Búsqueda inductiva de datos y proyectos de investigación en lengua materna - Dussán, Éder García (Enunciación, 2016)
The article discusses the problem of how to start a research process in the field of school communication in a mother language and, in order to guide a path that will allow progress in this regard, it exposes the phases that requires a teacher-researcher for the construction of a research project as a precondition for systematic expression of a research problem which takes as its object of study linguistic processes such as reading, writing, speaking, listening or aesthetic experiences. To achieve this, we take into account the principles of the proposal of Tamayo and Tamayo (2004), which are exemplified by a hypothetical case that reveals the details that precede the writing of a project and, therefore, to the consolidation of the constitutive items of the syntaxes of a research problem. The result of this effort shows the usefulness of inductive reasoning concerning the intention to obtain pedagogical knowledge through inquiry from the classroom to the school performers.